Social Capital and Post‐Conflict Reconstruction in Burundi: The Limits of Community‐based Reconstruction. Issue 1 (14th January 2013) - Vervisch, Thomas; Titeca, Kristof; Vlassenroot, Koen; Braeckman, Johan
ABSTRACT Using an examination of three NGO interventions in post‐conflict Burundi, this article questions community‐based reconstruction as a mechanism to rebuild social capital after conflicts, particularly when direct livelihood support is provided. The authors demonstrate a general shortcoming of the methodology employed in community‐based development (CBD), namely its focus on 'technical procedural design', which results in what may be termed 'supply‐driven demand‐driven' reconstruction. The findings suggest the need for a political economy perspective on social capital, which acknowledges that the effects on social capital are determined by the type of economic resource CBD gives access to. Through the use of a resource typology, the case studies show that the CBD methodology and the potential effects on social capital differ when applied to public and non‐strategic versus private and strategic resources. This has particular consequences for post‐conflict situations. A generalized application of CBD methodology to post‐conflict reconstruction programmes fails to take adequate account of the nature of the interventions and the challenges posed by the particular post‐conflict setting. The article therefore questions the current popular 'social engineering' approach to post‐conflict reconstruction.